The ‘Great prince’ Chesar Orbelian and Chesar’s palace as a unique monument of historical and cultural heritage - Grigoryan, Avetis; Vasilyan, Levon; Danielyan, Hayk; Eghiazaryan, Arman; Baghdasaryan, Anna; Simonyan, Astghik; Zakyan, Tigran; Arzumanyan, Astghik; Babayan, Susanna; Simonyan, Hasmik (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
The village Hors in Armenia’s Vayots Dzor province was the residence of one of medieval Armenia’s prominent noble dynasties – the Orbelian family. The ruins of a palatial complex, considered to be one of the finest surviving examples of 13th-14th-century Armenian civil architecture, are located here, along with a collapsed single-nave church adjacent to the palace, and inscriptions commemorating prince Chesar Orbelian, son of prince of princes Liparit, and his wife, Princess Khorishah. In 2024, the expedition team of the ‘Service for the Protection of Historical Environment and Cultural Museum-Reserves’ SNCO at the Ministry of Education, Science, Culture, and Sports of the Republic of Armenia conducted excavations in Hors, followed by a restoration project for the central building of the medieval palace complex and the adjacent church. Excavations revealed that the palace’s central structure had been surrounded by interconnected annexes of residential and economic significance. A dating inscription carved on one of the construction stones of the single-nave church supports its connection to the period of Chesar Orbelian’s rule and the nearby palace attributed to him. The column bases discovered in both the palace and the church suggest the presence of other monumental structures in the vicinity, which are now lost. The study of written and epigraphic primary sources allows for a fuller picture of Prince Chesar Orbelian’s life and activity, while the pottery fragments, mostly dated to the 13th-14th centuries found during the excavations, enrich our understanding of daily life within and around the medieval noble palace. The child burials discovered in the upper layer of the church are particularly noteworthy and require further historical-comparative and laboratory analysis to determine the circumstances and cause of death, their possible interrelation, and the date of the burials.